Heuristic Exchange 2Opt Best Improvement_r and Level of Efficacy of the solutions of the Symmetric Travelling Salesman Problem - Astoquillca-Yaranga, David J. (2023)
In this research, a hybrid algorithm called VMC_2OptBI_r was developed, which improved the solution search criteria applied by the 2Opt Exchange Heuristic based on a node exchange policy called Best Improvement (BI) and introducing an additional factor "1+r" to perform the 2Opt exchanges. The "1+r" factor allows slightly modifying the selection of nodes to be exchanged, thus exploring new solutions. To measure the level of efficacy of the new algorithm, instances of the Symmetric Traveling Salesman Problem from TSPLIB were selected and compared with their basic versions: Nearest Neighbor (VMC) and VMC_2OptBI. Then, they were compared with the solutions of the SCA_2Opt and SCA_2Opt_r algorithms, where they were compared with the solutions of four metaheuristics published in recent articles (2019-2022). The results showed that the solutions obtained by the new VMC_2OptBI_r algorithm achieved an efficacy level of 100% compared to VMC, VMC_2OptBI, SCA_2Opt, a value higher than 81% compared to SCA_2Opt_r, and a range between 11% to 88% compared to the four reviewed metaheuristics for the compared instances.